Association of systemic inflammation response index with latent tuberculosis infection and all-cause mortality: a cohort study from NHANES 2011-2012 - Wang, Lin; Kuang, Yi; Zeng, Yan; Wan, Zhihui; Yang, Sha; Li, Renliang (Frontiers in Immunology, 2025)
BackgroundThe Systemic Inflammatory Response Index (SIRI) is a promising inflammatory marker; however, the relationship between SIRI and latent tuberculosis infection (LTBI), as well as its association with mortality rates, remains unclear. The present study aimed to explore the associations of the SIRI with LTBI and all-cause mortality.MethodsWe conducted a prospective cohort study using data from National Health and Nutrition Examination Survey (NHANES) cycles from 2011 to 2012. We explored the association between SIRI and LTBI prevalence using Multiple logistic regression models. We used Multivariate Cox proportional hazards model to analyze the association between SIRI and all-cause mortality. In addition, Kaplan-Meier curves, restricted cubic splines (RCS), stratified analysis, and interaction tests were performed.ResultsThe study included a total of 4,983 adults who participated in NHANES 2011-2012. The mean follow-up period was 92.35 ± 16.82 months, and there were 525 deaths, representing a mortality rate of 10.54%. The occurrence of LTBI is significantly associated with low SIRI levels(OR=0.76, 95% CI: 0.66-0.89), after adjusting for confounders. Among LTBI patients, elevated SIRI levels are significantly correlated with an increased risk of all-cause mortality (adjusted HR = 1.48, 95% CI: 1.01-2.15). RCS revealed a linear relationship between SIRI and all-cause mortality in patients with LTBI (P =0.059[overall] and P = 0.391 [Nonlinear]). Furthermore, within the LTBI population, the area under the curve (AUC) of SIRI for all-cause mortality are 0.731 (1-year), 0.640 (3-year), and 0.634 (5-year).ConclusionThe findings of this study indicate that elevated SIRI levels are independently associated with an increased risk of all-cause mortality in patients with LTBI. Notably, SIRI was significantly inversely associated with the incidence of LTBI. Therefore, SIRI may serve as an effective tool for risk stratification in adults with LTBI in the United States. Further research is needed to elucidate the underlying mechanisms and to explore any therapeutic implications of these findings.